Childhood dental fear in the Netherlands: prevalence and normative data - ten Berge M, Veerkamp JSJ, Hoogstraten J, Prins PJM (Blackwell Synergy, 2002)
This study aimed to present normative data on dental fear for the Dutch child population, by identifying not only highly fearful children but also children at risk for developing this high dental fear.